2011
DOI: 10.1590/s1809-98232011000100011
|View full text |Cite
|
Sign up to set email alerts
|

Perfil socioeconômico-cultural de uma universidade aberta à terceira idade: reflexo da realidade brasileira?

Abstract: OBJETIVO: comparar os dados socioeconômicos e culturais de alunos de uma Universidade Aberta à Terceira Idade de uma instituição de ensino superior pública alagoana aos dados equivalentes do Estado de Alagoas da população brasileira de mesma faixa etária. MÉTODO: estudo transversal comparativo, realizado com os 460 participantes das três primeiras turmas da Universidade Aberta à Terceira Idade (UATI) de uma universidade pública de Alagoas. Compararamse às populações do estado de Alagoas e do Brasil: sexo, idad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 12 publications
(25 reference statements)
0
3
0
8
Order By: Relevance
“…This heterogeneity is not echoed in the Unatis, whose unique context cannot be extrapolated to the national scenario. Regarding this observation, Roque et al [7] reported that Unati members are mostly women, with higher schooling levels (78.7% > 9 years of study) and more economically active than the average Brazilian older population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This heterogeneity is not echoed in the Unatis, whose unique context cannot be extrapolated to the national scenario. Regarding this observation, Roque et al [7] reported that Unati members are mostly women, with higher schooling levels (78.7% > 9 years of study) and more economically active than the average Brazilian older population.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies [7,8] have characterized the sociodemographic profile and the physical activity level of older people at Universities of the Third Age (Unati), there are research gaps regarding their relationship with psychological aspects. The authors found that more involvement in the Unati for more than one year is associated with lower depressive symptom scores [8,9] and better perceived quality of life in the physical, psychological and social domains [8].…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, the studied groups had more women, similarly to what was observed in the total sample of older persons participants in the research, both due to the feminization of old age (in 2014, 55.7% of Brazilian older adults were women; IBGE 2015), and to the fact that older women tend to engage more in social interactions (Neri 2007), which could explain their greater interest in this type of activity. This prevalence of women among participants of educational or cultural activities is repeatedly observed, for example, in Brazilian Third Age Universities for (Castro et al 2007;Irigaray and Schneider 2008;Pinto 2009;Alexandre et al 2009;Souza and Russo 2009;Kretzer et al 2010;Sonati et al 2010;Roque et al 2011;Cachioni 2012). According to Debert (1999), while women represent the majority of participants in Third Age Universities and Community Centers, older K men usually are members of associations, federations and confederations of retirees or professional trade unions.…”
Section: Participantsmentioning
confidence: 77%
“…Esse tipo de auto avaliação vem sendo considerada um indicador de saúde tão importante quanto os dados objetivos. (Roque et. al., 2011;Blazer, 2014).…”
Section: Métodounclassified
“…Nesse sentido, a capacidade de interação social é essencial para o idoso estabelecer e manter suas redes de apoio social e garantir maior qualidade de vida (Araújo et al, 2011).…”
unclassified